PENGUKURAN MUTU LAYANAN DAN KEPUASAN KONSUMEN SPBU 44.574.14 KABUPATEN KLATEN - Suhendro, Suhendro; Suranto, Much; Supratikno, Supratikno; Prakosa, Cucut; Nugroho, Arif Julianto Sri; Setianingtyas, Anna Febrianty; Santoso, Agus (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
This study aimed to examine the gap between customer service expectations and perceptions at gas station in SPBU 44.574.14 Klaten. The test of the model used Servqual Test. The research design was quantitative. The formulation of the hypothesis used the Cronin Taylor Importance Servqual Test formula. The consumer population were all consumers and a sample of consumers at this gas station were those who were adults when they had finished getting service at the gas station. The sampling technique was purposive as many as 95 consumers. The test results show that the responsiveness dimension has the largest gap value. Manajemen must improve the service which still provides the largest gap value followed by the next gap value.